Charting new horizons: 2023 media coverage report - diversification initiatives in East and Southern Africa - Nkosi, Phindiwe (International Water Management Institute (IWMI), 2023)
This media report delves into the dynamic landscape of economic transformation, examining regional efforts to diversify industries, foster innovation, and attract investments. From agricultural initiatives to green energy projects, we analyze the multifaceted approaches shaping the future. Unveiling trends, analyzing key initiatives, and decoding media perspectives, the report offers an insightful exploration of how the media landscape has influenced and reflected the dynamic economic transformation unfolding across East and Southern Africa throughout the year 2023.